2011
DOI: 10.1099/mic.0.052407-0
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis reveals that ClpXP proteolysis controls key virulence properties of Streptococcus mutans

Abstract: The ClpXP proteolytic complex is critical for maintaining cellular homeostasis, as well as expression of virulence properties. However, with the exception of the Spx global regulator, the molecular mechanisms by which the ClpXP complex exerts its influence in Streptococcus mutans are not well understood. Here, microarray analysis was used to provide novel insights into the scope of ClpXP proteolysis in S. mutans. In a DclpP strain, 288 genes showed significant changes in relative transcript amounts (P¡0.001, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 51 publications
1
28
0
Order By: Relevance
“…In fact, this is the case in S. thermophilus where CRISPR-Cas systems were observed to function independently (86). Furthermore, several transcriptome studies revealed that deletion of virulence or global regulatory genes of S. mutans (including genes involved in stress response) differently affected transcription of cas genes within CRISPR-Cas systems, suggesting different roles for cas genes within the cell (50,54,87). As already proven in other systems (88-91), it is possible that different regulatory systems, in addition to VicR/K, interact with S. mutans CRISPR-Cas systems to mediate gene expression in response to cues such as oxidative stress and cell membrane changes or alterations in the internal pH of the cell.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, this is the case in S. thermophilus where CRISPR-Cas systems were observed to function independently (86). Furthermore, several transcriptome studies revealed that deletion of virulence or global regulatory genes of S. mutans (including genes involved in stress response) differently affected transcription of cas genes within CRISPR-Cas systems, suggesting different roles for cas genes within the cell (50,54,87). As already proven in other systems (88-91), it is possible that different regulatory systems, in addition to VicR/K, interact with S. mutans CRISPR-Cas systems to mediate gene expression in response to cues such as oxidative stress and cell membrane changes or alterations in the internal pH of the cell.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, it was shown that M102 adheres to phage-sensitive and phage-resistant S. mutans serotype c strains, indicating that factors besides phage adsorption determine resistance of S. mutans serotype c strains to infection by M102 phage (49). Despite these studies that explored the role of CRISPR-Cas systems in S. mutans in conferring phage immunity, recent transcriptome studies suggest other functions that CRISPR-Cas systems might have in S. mutans are poorly understood (50)(51)(52)(53)(54)(55).…”
mentioning
confidence: 99%
“…Although ClpL is required for growth at 43°C and for penicillin tolerance (478,483), an S. pneumoniae ⌬clpL mutant showed a level of virulence similar to that of the parental strain in a murine intraperitoneal infection model (478). Systematic deletion of clpP and the five Clp ATPase genes (clpB, clpC, clpE, clpL, and clpX) in the dental pathogen S. mutans revealed that the ClpXP proteolytic system modulates the expression of several virulence-related traits (304,484) and that the infectivity of strains lacking clpP or clpX is slightly reduced in a rat model of oral colonization (304). Inactivation of the remaining Clp ATPases did not affect tooth colonization, but the role of the S. mutans Clp proteins in caries development or in infective endocarditis remains to be evaluated further.…”
Section: General Stress Responses and Virulencementioning
confidence: 99%
“…In Streptococcus mutans, the causative agent of tooth decay, mutations in virulence or global regulatory genes (including genes involved in stress responses) strongly affect gene transcription (81)(82)(83)(84)(85), including that of the type II cas genes ( Fig. 1 and 4).…”
Section: Transcriptome Analysis Of the Cas Genesmentioning
confidence: 99%